2017
DOI: 10.1142/s0219887817501389
|View full text |Cite
|
Sign up to set email alerts
|

ER = EPR and non-perturbative action integrals for quantum gravity

Abstract: International audienceIn this paper, we construct and calculate non-perturbative path integrals in a multiply-connected spacetime. This is done by summing over homotopy classes of paths. The topology of the spacetime is defined by Einstein–Rosen bridges (ERB) forming from the entanglement of quantum foam described by virtual black holes. As these “bubbles” are entangled, they are connected by Planckian ERBs because of the ER = EPR conjecture. Hence, the spacetime will possess a large first Betti number B1. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…De facto, we have shown that our model for UMF is background independent [25,249,248], i.e. it does not assume a fixed background (see how we can change the conditions) and by definition is built by the sum of the contributions of all the entities and so dynamic by nature at all time; something believed by many to be key to ensure correct modelling / avoidance of graviton selfinteractions 88 [248] and essential to align with GR that we need to recover at semi classical and classical scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…De facto, we have shown that our model for UMF is background independent [25,249,248], i.e. it does not assume a fixed background (see how we can change the conditions) and by definition is built by the sum of the contributions of all the entities and so dynamic by nature at all time; something believed by many to be key to ensure correct modelling / avoidance of graviton selfinteractions 88 [248] and essential to align with GR that we need to recover at semi classical and classical scales.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, this includes adding dimensions to spacetime and modifying the Hilbert-Einstein Action to achieve such cancellation at higher orders. 88 Because of the need to model through them the back reaction when the background is fixed as in QFT and superstring theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation